Pengaruh Daya Saing, Gender, Fraud Diamond Terhadap Perilaku Kecurangan Akademik Mahasiswa - Yozi Andayani; Vita Fitria Sari (Universitas Negeri Padang, 2019)
Academic fraud is something that has a devastating effect on students just for a satisfying outcome. So they forget the purpose of the actual education itself. There are factors that encourage someone to commit fraud found in the theory of diamond fraud developed by Cressey (1953), namely pressure, opportunity, rationalization and ability. In the research there are new factors that might influence academic fraud namely competitiveness. Unlike the previous research, in this study using competitiveness and gender variables. Where this competitiveness is one of the factors to encourage someone to commit academic fraud, because the competitiveness of individuals in getting the best value is very stimulating the individual to do what is desired by utilizing the situation and capabilities. The purpose of this study was to determine the cause of someone doing academic fraud. From the results of the research that has been done, it is known that what affects the occurrence of fraud in the academy is opportunity and also gender differences.